Analysis Of The Factors Causing The Non-Dance Credit At PT Hemas Parama - Yuniarso, Yudi Budi; Estiningsih, Wening (International Journal of Informatics, Economics, Management and Science, 2023)
The problem of bad credit is a serious issue in the banking industry that can have a significant impact on the financial health of a company. This study aims to analyze the factors that cause bad credit at PT. Hemas Parama. Literature review was conducted to understand the concept of bad credit, risk management theory, and the factors that cause bad credit that are generally identified in the banking industry. Through a review of the literature, factors such as economic factors, ineffective risk management, changes in customer conditions, and internal company factors have been identified as common causes of bad debts. In addition, best practices in managing credit risk and the role of technology and analytics in identifying risk factors are also obtained from the literature. This literature review describes an in-depth conceptual framework for analyzing the causes of bad credit at PT. Hemas Parama. This study has practical implications by generating a better understanding of the factors that can lead to bad credit in these companies. The results of this study can be used to formulate more effective risk management strategies and solutions that can help reduce the risk of bad credit. Thus, this research is expected to provide valuable insights for PT. Hemas Parama in overcoming bad credit challenges and improving company financial performance.   Keywords : Bad credit Credit risk management Factors causing bad credit banking industry PT. Hemas Parama